MENAKAR PERILAKU PROFESIONAL DALAM RANGKA MENINGKATKAN KINERJA APARATUR BIROKRASI - Derajad S. Widhyharto (Jurnal Manajemen Kepegawaian, 2008)
Having word about civil servants professional behavior, we are leaded to imagine good dedication, commitment to serve, fulfilling need of safety, and also protecting civil society. Actually, it is quite difficult to have civil servants professional behavior in daily life. We can also find a big hole between wishes and hope toward civil servants professional behavior. Perceiving civil servants professional behavior as a profession commitment is one effort to make the hole closer. It means that choosing civil servants as a profession need no reward punishment system. Civil servants will do their profession rationally with good dedication, and also manage their work according to the rule. These we identified as commitment. When we use that definition, we have to prepare many things as the consequences. Appropriate payment and social welfare will be among of those. Keywords: civil servants, Foucault, Authority, Professional Behavior